2016
DOI: 10.4103/0976-3147.172170
|View full text |Cite
|
Sign up to set email alerts
|

Hindi translation and evaluation of psychometric properties of Craig Hospital Inventory of Environmenta Factors instrument in spinal cord injury subjects

Abstract: Introduction:The Craig Hospital Inventory of Environmental Factors instrument (CHIEF) is one of the few tools to assess the environmental barriers. The purpose of this study was to translate long and short CHIEF into Hindi language, and to determine its validity and reliability.Design and Setting:The study design was observational case series with repeated measures. It was carried out at Indian Spinal Injuries Centre New Delhi, a specialized center for rehabilitation for spinal cord injury.Methods:The CHIEF in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Test-retest reliability and internal consistency reliability of the instrument are similar to what Whiteneck et al [10] found. For example, in the study among Chinese people with stroke, ICC ¼ 0.845 and Cronbach a ¼ 0.93 were reported [19] and in a study among people with spinal cord injury, the Hindi version demonstrated ICC ¼ 0.80 and Cronbach a ¼ 0.92 [23]. The Brazilian version [24] used among children and [21] this assessment has showed cognitive impairment to a greater extent compared to an objective assessment.…”
Section: Chief-smentioning
confidence: 97%
See 1 more Smart Citation
“…Test-retest reliability and internal consistency reliability of the instrument are similar to what Whiteneck et al [10] found. For example, in the study among Chinese people with stroke, ICC ¼ 0.845 and Cronbach a ¼ 0.93 were reported [19] and in a study among people with spinal cord injury, the Hindi version demonstrated ICC ¼ 0.80 and Cronbach a ¼ 0.92 [23]. The Brazilian version [24] used among children and [21] this assessment has showed cognitive impairment to a greater extent compared to an objective assessment.…”
Section: Chief-smentioning
confidence: 97%
“…adolescents with cerebral palsy also demonstrated ICC 0.92. In addition, Soni et al [23] determined the content validity ratio to be 1.00 for all the items except item number 5, 11, and 12. The overall content validity index was 0.97 for the longer version.…”
Section: Chief-smentioning
confidence: 99%
“…Module C uses 12 selected questions from the CHIEF instrument [28]. This instrument has been implemented and validated in several LMICs [31][32][33][34][35][36]. The first 3 questions ask whether the participants have the same opportunities as other people to participate and take advantage of the areas of education, employment, and leisure.…”
Section: Follow-up Data Collectionmentioning
confidence: 99%